Safety and performance of transbronchial cryobiopsy for parenchymal lung lesions - Herth, Felix; Mayer, Max; Thiboutot, Jeffrey; Kapp, Christopher M.; Sun, Jiayuan; Zhang, Xiaoju; Herth, Jonas; Kontogianni, Konstantina; Yarmus, Lonny (Chest, 2021)
Background - Despite advances in technology, the bronchoscopic diagnosis of parenchymal pulmonary lesions (PPLs) remains difficult to achieve. Transbronchial lung cryobiopsy (TLCB) offers the potential for larger samples with improved diagnostic yield; however, a paucity of data exists describing its safety and usefulness for the diagnosis of PPL. - Research Question - What is the safety profile of TLCB for PPL? - Study Design and Methods - An observational, retrospective, multicenter cohort study enrolled patients without endobronchial disease undergoing TLCB of PPL from 2015 through 2019. All procedures were performed using both rigid and flexible bronchoscopy with a flexible cryoprobe. Complication rates, including bleeding and pneumothorax rates, were collected. Bleeding was graded on a scale from 0 (trace) to 4 (requiring surgical intervention) with a grade of ≥ 3 considered clinically significant. Pneumothorax, tube thoracostomy placement, diagnostic yield, and need for subsequent interventions were recorded. - Results - One thousand twenty-four patients underwent TLCB. One hundred eighty-eight patients (18%) experienced bleeding; in 36 patients (3.5%), the bleeding was clinically significant. Sixty-eight patients (6.6%) demonstrated a pneumothorax and 64 patients (6.3%) required drainage with tube thoracostomy. All chest drains were removed within 4 days, and no cases of prolonged air leak occurred. A definitive diagnosis was achieved in 932 patients (91%). Adenocarcinoma (46%) and metastatic disease (21%) were the most common diagnoses. - Interpretation - TLCB showed an acceptable safety profile and diagnostic yield for the evaluation of PPL in this large retrospective cohort. Prospective clinical trials are underway to validate these findings further.